ZrFsy1, a high-affinity fructose/H+ symporter from fructophilic Zygosaccharomyces rouxii - Leandro, Maria José (2019)
Zygosaccharomyces rouxii is a fructophilic yeast than can grow at very high sugar concentrations. We have identified an ORF encoding a putative fructose/H+ symporter in the Z. rouxii CBS 732 genome database. Heterologous expression of this ORF in a S. cerevisiae strain lacking its own hexose transporters (hxt-null) and subsequent kinetic characterization of its sugar transport activity showed it is a high-affinity low-capacity fructose/H+ symporter, with Km 0.4560.07 mM and Vmax 0.5760.02 mmol h21 (gdw) 21. We named it ZrFsy1. This protein also weakly transports xylitol and sorbose, but not glucose or other hexoses. The expression of ZrFSY1 in Z. rouxii is higher when the cells are cultivated at extremely low fructose concentrations (,0.2%) and on non-fermentable carbon sources such as mannitol and xylitol, where the cells have a prolonged lag phase, longer duplication times and change their microscopic morphology. A clear phenotype was determined for the first time for the deletion of a fructose/H+ symporter in the genome where it occurs naturally. The effect of the deletion of ZrFSY1 in Z. rouxii cells is only evident when the cells are cultivated at very low fructose concentrations, when the ZrFsy1 fructose symporter is the main active fructose transporter system